Rational Selection Of Proton Pump Inhibitors (Ppis) Through An Objective Scoring System For Effective Formulary Management - Lim, Lynette, Chu Ann (2011)

(untitled)
Pemilihan ubat secara rasional adalah penting dalam pengurusan formulari yang berkesan.